Dynamic study of the light soaking effect on perovskite solar cells by in-situ photoluminescence microscopy. (April 2018) - Deng, Xiaofan; Wen, Xiaoming; Zheng, Jianghui; Young, Trevor; Lau, Cho Fai Jonathan; Kim, Jincheol; Green, Martin; Huang, Shujuan; Ho-Baillie, Anita
Abstract: Organic-inorganic halide perovskite solar cells (PSCs) have emerged as promising candidates for next generation solar cells due to the rapid increase in their power conversion efficiency. The instability of these cells under illumination, however, remains a major technical barrier for commercialization. In this work, by fabricating full perovskite cells (not test structures) that is compatible with in photoluminescence (PL), for the first time we have achieved in-situ monitoring of the localized charge carrier and ion dynamics in an operating perovskite solar cell under light soaking, using nanoscale resolved in-situ PL and time-resolved PL (tr-PL) microscopy. By analyzing the dynamic PL lifetime and intensity under different light soaking conditions and its correlation with the shape of the voltage current curve, we explain the different scenarios of ion migration and accumulation at the interface and in the bulk that result in different hysteresis behaviors. Our results suggest that mobile positive ions, predominantly iodide vacancies pre-accumulate near the spiro-MeOTAD/perovskite interface of as-fabricated devices, reducing charge-carrier separation and increasing recombination at that electrode. After light soaking for a short time at open circuit, these positive ions drift away from the interface under the altered electric field, improving device performance. After prolonged light soaking, however, negative ions, predominantly iodide interstitials drift to the spiro-MeOTAD/perovskite interface, significantly enhancing carrier recombination at that electrode. In contrast, light soaking had less effect at short-circuit because the electric field is invariant at short circuit. In addition to the light-soaked-induced ion movement under short circuit is by diffusion rather than by drift. This result in ionic redistribution and ion-recombination increases PL intensity uniformity across the device and resulting in relatively stable device performance. Our work reveals that the bias voltage during light soaking results in different dynamic processes, which can be either positive or negative. Analysis on the corresponding PL images revealed a difference in charge carrier and ion dynamics between grain interior and grain boundary during light soaking. The larger density of grain boundaries causes a faster ion migration rate in the regions with smaller grains. Therefore, it may be possible to reduce J-V hysteresis by producing larger grains. Our results provide novel insight into the effect of light soaking on ions and subsequent effect on carrier dynamics for better understanding of the operation of perovskite solar cells. Graphical abstract: fx1 Highlights: Complete perovskite solar cell (not test structure) compatible with photoluminescence microscopy is fabricated. The in-situ study of localized charge carrier dynamics during light soaking is performed. Dynamic PL under different light soaking conditions and its correlation with the shape of the JV curve are investigated. High resolution PL microscopy reveals different charge carrier and ion dynamics between grain interior and grain boundary.